REVIEW: Vibrant, stimulating view of region's nationalism, media - Alan Robson (Asia Pacific Network, 1995)
Review of: Blood on their Banner: Nationalist Struggles in the South Pacific, by David Robie. London, Zed Books, 1989; Sydney: Pluto Press, 1990; Manila: Malaya Books, 1991.